An Exploratory Meta-Analytic Review on the Empirical Evidence of Differential Learning as an Enhanced Motor Learning Method - Tassignon, Bruno; Verschueren, Jo; Baeyens, Jean-Pierre; Benjaminse, Anne; Gokeler, Alli; Serrien, Ben; Clijsen, Ron (Frontiers in Psychology, 2021)
Background: Differential learning (DL) is a motor learning method characterized by high amounts of variability during practice and is claimed to provide the learner with a higher learning rate than other methods. However, some controversy surrounds DL theory and to date, no overview exists that compares the effects of DL to other motor learning methods. Objective: To evaluate the effectiveness of DL in comparison to other motor learning methods in the acquisition and retention phase. Design: Systematic review and exploratory meta-analysis. Methods: PubMed (MEDLINE), Web of Science and Google Scholar were searched until 3 February 2020. To be included, (1) studies had to be experiments where the DL group was compared to a control group engaged in a different motor learning method (lack of practice was not eligible), (2) studies had to describe the effects on one or more measures of performance in a skill or movement task, and (3) the study report had to be published as a full paper in a journal or as a book chapter. Results: Twenty-seven studies, encompassing thirty-one experiments were included. Overall heterogeneity for the acquisition phase (post-pre; I²= 77%) as well as for the retention phase (retention-pre; I²= 79%) was large, and risk of bias was high. The meta-analysis showed an overall small effect size of 0.26 [0.10, 0.42] in the acquisition phase for participants in the DL group compared to other motor learning methods. In the retention phase, an overall medium effect size of 0.61 [0.30, 0.91] was observed for participants in the DL group compared to other motor learning methods. Discussion/conclusion: Given the large amount of heterogeneity, limited number of studies, low sample sizes, low statistical power, possible publication bias and high risk of bias in general, inferences about the effectiveness of DL would be premature. Even though DL shows potential to result in greater average improvements between pre- and post/retention test compared to non-variability based motor learning methods, more high-quality research is needed before issuing such a statement. For robust comparisons on the relative effectiveness of DL to different variability-based motor learning methods, scarce and inconclusive evidence was found.